2021
DOI: 10.1093/humrep/deab149
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of the effects of increased energy intake on menstrual recovery in exercising women with menstrual disturbances: the ‘REFUEL’ study

Abstract: STUDY QUESTION Does increased daily energy intake lead to menstrual recovery in exercising women with oligomenorrhoea (Oligo) or amenorrhoea (Amen)? SUMMARY ANSWER A modest increase in daily energy intake (330 ± 65 kcal/day; 18 ± 4%) is sufficient to induce menstrual recovery in exercising women with Oligo/Amen. WHAT IS KNOWN ALREADY Optimal energy availabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…Moreover, low EA could also lead to disturbances of a plethora of hormones, such as cortisol, growth‐hormone/insulin growth factor 1, thyroid hormones, and others 47 . Accordingly, increasing energy intake in athletes with menstrual dysfunction has been shown to improve menstrual cycle recovery 48 . The term female athlete triad encompasses the spectrum of restrained eating (low EA), menstrual dysfunction, and poor bone health, associated with increased risk of stress fractures and osteopenia or osteoporosis later in life 49 .…”
Section: Energy Availability and Associated Risk Factors In Female Fo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, low EA could also lead to disturbances of a plethora of hormones, such as cortisol, growth‐hormone/insulin growth factor 1, thyroid hormones, and others 47 . Accordingly, increasing energy intake in athletes with menstrual dysfunction has been shown to improve menstrual cycle recovery 48 . The term female athlete triad encompasses the spectrum of restrained eating (low EA), menstrual dysfunction, and poor bone health, associated with increased risk of stress fractures and osteopenia or osteoporosis later in life 49 .…”
Section: Energy Availability and Associated Risk Factors In Female Fo...mentioning
confidence: 99%
“…47 Accordingly, increasing energy intake in athletes with menstrual dysfunction has been shown to improve menstrual cycle recovery. 48 The term female athlete triad encompasses the spectrum of restrained eating (low EA), menstrual dysfunction, and poor bone health, associated with increased risk of stress fractures and osteopenia or osteoporosis later in life. 49 The more recent broader term "relative energy deficiency in sports" (RED-S) includes a wider set of health and performance outcomes, such as metabolic rate, immunity, and protein synthesis rate.…”
Section: Energy Availability and Associated Risk Factors In Female Fo...mentioning
confidence: 99%
“…Exercise-induced menstrual disorder (EAMD) is a special medical problem that perplexes female athletes and coaches, including exercise-induced amenorrhea (AA), sparse menstruation, anovulatory cycle, and luteal insufficiency (LPD) [ 1 ]. According to the severity of EAMDs, the order from severe to mild was amenorrhea, sparse menstruation, anovulatory cycle, and LPD [ 2 ]. Although exercise-induced amenorrhea is the most serious form of menstrual disorders, other forms of menstrual disorders can also lead to lower levels of estrogen and progesterone and affect the health, bone health, and fertility of athletes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lifestyle changes, such as increasing caloric intake and reducing physical exercises, and cognitive behavioral therapy (CBT) aimed at alleviating psychological stressors, are commonly used non-pharmacological treatment strategies for improving reproductive function and hormonal and energy metabolic status, but not bone health ( 25 ). Some observations and clinical trials have indicated that diet interventions that increase the caloric intake for overtraining female athletes with FHA could ameliorate their reproductive function ( 64 , 65 ). Both CBT and hypnotherapy, which are common psychotherapies in clinical practice, can result in follicular growth and ovulation ( 66 ).…”
Section: Resultsmentioning
confidence: 99%